Effects of conjugated fatty acid supplementation on central obesity and blood pressure in women with benign breast disease: a randomized controlled-clinical trial - Pirouzpanah, Saeed; Montazeri, Vahid; Baradaran, Behzad; Taghizadeh, Mohsen; Rezvani, Neda (Progress in Nutrition, 2018)
Objective: Health benefits of conjugated fatty acids, particularly conjugated linolenic acid (CLNA), have recently provide substantial insights in a variety of obesity-related tumorigenesis including breast neoplasia. This study aims to investigate the effects of CLNA-contained oil (CLNAO) supplementation on central obesity indices and blood pressure in women with benign breast disease (BBD). Methods: Forty six pre-menopausal women with BBD were randomly allocated to intervention group (n=23) or placebo (n=23). Patients in the intervention group received 1000 mg/day CLNAO capsule and the placebo group received 1000 mg/day inert oil-contained capsule during 13 weeks. Measures of blood pressure and some anthropometric variables were performed at the baseline and end of study. Result: Systolic (P